Trastuzumab-induced cardiotoxicity and role of mitochondrial connexin43 in the adaptive response. (September 2020) - Pecoraro, Michela; Pinto, Aldo; Popolo, Ada
Abstract: Trastuzumab, the humanized monoclonal antibody specific for HER2 receptor, is the gold standard in the treatment of HER2+ breast cancer. Despite its high therapeutic efficacy, cardiotoxicity has emerged as a significant side effect. The molecular mechanisms involved are not well understood, but all converge on mitochondria. Mitochondrial Cx43 can confer cardioprotection by regulating mitochondrial calcium homeostasis, ROS production and propagation of apoptotic signals, and studies report that it is overexpressed both in ischemic preconditioning and in Doxorubicin-induced cardiotoxicity. This study was designed to evaluate whether mitochondrial Cx43 (mCx43) is also involved in Trastuzumab-induced cardiotoxicity. Here we demonstrated that mCx43 is overexpressed in Trastuzumab-treated H9c2 cells. Our data showed that inhibition of Cx43 translocation to mitochondria, obtained by radicicol pre-treatment, significantly increases cytosolic and mitochondrial superoxide formation, mitochondrial membrane depolarization and the consequent apoptosis induced by Trastuzumab. Our results support the hypothesis that disruption of mitochondrial function is the principal mechanism by which Trastuzumab elicits its cardiotoxicity and mCx43 appears to counteract the Trastuzumab-induced mitochondrial damage. Highlights: Trastuzumab elicits its cardiotoxicity by mitochondrial disruption. Trastuzumab administration increases mitochondrial Cx43 expression. Mitochondrial Cx43 appears to counteract the Trastuzumab-induced mitochondrial damage.